Caesar Chiper Algorithm In Message Security - Wasis (Jurnal Inotera, 2026)
The Caesar Cipher algorithm is one of the classical cryptography methods used to secure messages with letter substitution techniques based on certain shifts in the alphabet. This study aims to analyze and implement this algorithm in message security in order to understand its effectiveness and limitations in the world of information security. The methods used include encryption and decryption processes with character shifts according to the specified key. Implementation is carried out using the Python programming language as a case study. The results of the study show that Caesar Cipher is effective in providing basic security for messages, but has significant weaknesses against brute force attacks because it only has 25 possible keys. Therefore, this algorithm is more suitable for use as a basis for learning in the field of cryptography or combined with other security methods to increase its level of security.